Consumer preferences for biofortified iron beans: Results from a willingness to pay and choice experiment in Kenya - Obebo, Forah; Ateka, Josiah; Kioo, Juliana; Mwangi, Christine (VeriXiv, 2025)
Micronutrient deficiency is a public health issue in many developing countries including Kenya. Despite the release of Biofortified Iron Beans (BIBS) to bridge the health burden, their adoption has been slow. Our study applies the willingness to pay (WTP) and choice experiments to assess preferences for BIB attributes among consumers. Using a dataset of 561 respondents, we compare the WTP among consumers in a large urban city (Nairobi) with those in a rural area (Bomet) where BIB production has been promoted. We test whether message framing (gain vs loss framed) has varied effects in the rural-urban context, following the prospect hypothesis. This study further utilises choice experiment to test the extent to which biofortification attribute is important for bean preferences. WTP results show that consumers are willing to pay a premium of 38.5 percent for the BIBs above the price of their preferred conventional beans (KES 165.7), signifying high acceptance. Rural respondents have a higher WTP (KES 71.06) than urban respondents highlighting the role of proximity to BIB production area. Consistent with prospect theory, male and urban respondents are willing to pay more under loss-frame messaging than gain-frame messaging, while female respondents are more responsive under gain-frame messaging. Surprisingly, awareness on nutrient enriched beans exhibits negative influence on WTP for the respondents exposed to gain-framed messaging. This may be due to consumers attaching public good properties to BIBs and therefore less willing to pay for biofortified traits. Results from the conditional logit model indicate biofortification is important for urban consumers and female-headed households. Based on the findings, there’s need for targeted nutrition education programming among rural-urban and male-female consumers. Considering that flatulence, cooking time and taste are main preferred attributes of BIBs, promotional messages that include these attributes could be used to accompany the biofortification messages to catalyze adoption.